The under investigated facet of the COVID-19 pandemic: Molecular analysis of secondary bacterial infections at a COVID dedicated intensive care unit within a tertiary care center in Lebanon - Sleiman, Ahmad; Abdelkhalek, Pascal; Doumat, George; Atallah, Frida; Hamadeh, Lama; Moussa, Pamela; Bou Akl, Imad; Dbaibo, Ghassan; Araj, George F.; Kanj, Souha S.; Mahfouz, Rami; Matar, Ghassan M.; et al. (Frontiers in Medicine, 2023)
Background The coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide. Secondary bacterial infections are associated with unfavorable outcomes in respiratory viral infections. This study aimed at determining the prevalence of secondary bacterial infections in COVID-19 patients admitted at a tertiary medical center in Lebanon and evaluating the seriousness of these infections. Methodology From May till November, 2020, a total of 26 Gram-negative isolates were recovered from 16 patients from various specimens during the course of their COVID-19 infection with Escherichia coli being the most prevalent. WAS THIS A RANDOM SAMPLE OR CONSECUTIVE PATIENTS? They were tested for their antimicrobial susceptibility by broth microdilution against 19 antimicrobial agents from different classes. Whole genome sequencing of 13 isolates allowed the mining of antimicrobial resistance determinants as well as mobile genetic elements and sequence types. Finally, Broth microdilution with 3 different efflux pump inhibitors (Theobromine, Conessine and PheArg-β-naphthylamide) was done. Results Antimicrobial susceptibility testing showed that out of the 26 Gram-negative isolates, 1 (4%) was extensively drug resistant and 14 (54%) were multi-drug resistant. Whole genome sequencing results revealed a plethora of antimicrobial resistance determinants among the 13 sequenced isolates. Moreover, the 9 and 4 sequenced Enterobacterales and Pseudomonas aeruginosa isolates belonged to 9 and 2 different sequence types, respectively. The efflux pump inhibitor assay results showed no change in the minimal inhibitory concentration of both ciprofloxacin and tetracycline once theobromine was added. Although the minimal inhibitory concentration of levofloxacin against the 3 P. aeruginosa isolates did not change after the addition of conessine, a significant change was detected in 2 isolates when PheArg-β-naphthylamide was added. Conclusion The identification of carbapenem and colistin resistant Gram-negative bacilli causing secondary bacterial infections should be of high concern. Accordingly, it is important to monitor secondary bacterial infections in critical patients diagnosed with COVID-19.